Association between age of starting clean intermittent catheterization and current urinary continence in individuals with myelomeningocele. Issue 5 (October 2022) - Freeman, Kurt A.; Liu, Tiebin; Smith, Kathryn; Castillo, Heidi; Castillo, Jonathan; Joseph, David; Wang, Yinding; Tanaka, Stacy
Summary: Introduction: Patients with myelomeningocele often use clean intermittent catheterization (CIC) for renal preservation and to promote urinary continence. While starting CIC at an early age is associated with better renal outcomes, the impact of age of CIC initiation on continence outcomes has not been examined. Objective: To examine whether earlier CIC initiation is associated with higher likelihood of current urinary continence for patients with myelomeningocele. Study design: Data of patients aged ≥5 years at last visit were obtained from 35 spina bifida clinics participating in the National Spina Bifida Patient Registry from 2013 to 2018. Sociodemographic characteristics, disease characteristics, and current bladder management strategies were collected. Via univariate and multiple logistic regression models, the latter conducted controlling for all variables associated with current continent status, associations between continence and sociodemographic factors, condition characteristics, and age CIC began (<3 years of age, 3–5 years, 6–11 years, ≥12 years) were analyzed. Results: Data from 3510 individuals were included (mean age at last visit = 17.0 years, range 5.0–88.7). The sample was evenly distributed by sex (52% female); most individuals were non-Hispanic White (62.6%). The majority of patients (55.2%) started CIC before age 3 years. Continence varied markedly across those who never started CIC (0.6% of patients were continent) and those who started at any age (range 35.3–38.5%). Among those who started CIC, the magnitude of the association was not proportional to age CIC was started. Compared with those who started CIC at age 12 or older, estimated adjusted odds ratio of being continent ranged from 1.04 (6–11 years, 95% CI, 0.72–1.52) to 1.25 (<3 years, 95% CI, 0.89–1.76). Discussion: Although CIC may be positively associated with achieving urinary continence in individuals with myelomeningocele, we could not demonstrate that younger age at CIC initiation increased the likelihood of achieving this goal. Limitations include lack of data on reason for starting CIC, urodynamic data, and the observational nature of data collection. Conclusions: Further study is needed addressing limitations of the current investigation to determine if urinary continence outcomes are influenced by the age of starting CIC among patients with myelomeningocele.